Dental Fear and Dental Health and Attendance among Finnish Male Prisoners - Raija Vainionpää; Paula Pesonen; Marja-Liisa Laitala; Vesa Pohjola; Vuokko Anttonen (eJournal of Oral Maxillofacial Research)
Objectives: The aim of the present study was to evaluate the prevalence of dental fear and the associations between dental fear and dental health and dental attendance among Finnish prisoners.